1991
DOI: 10.1017/s0890037x00033777
|View full text |Cite
|
Sign up to set email alerts
|

Response of Seedling Alfalfa (Medicago sativa) to Four Postemergence Herbicides

Abstract: Response of seedling alfalfa to four herbicides applied at the 2nd, 4th, and 8th trifoliate leaf stages was evaluated in 1988 and 1989. There was no interaction between the herbicides and alfalfa growth stages at the time of herbicide application in either year. Bentazon did not reduce alfalfa height or yield of the first cutting in either year. The dimethylamine salt of 2,4-DB and bromoxynil reduced first-cutting alfalfa yield in 1988 and 1989, respectively, and the butoxyethanol ester of 2,4-DB reduced first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…Several studies have shown that some herbicides can have initial phytotoxic effects, although seedlings usually recover without severe damage, and yield loss are not observed (Díaz et al 1992;Ivany et al 2002;Thomas et al 1994;Tonks et al 1991;Volenberg et al 2002;Young et al 2003). In other studies, however, various clover species were exposed and evaluated for tolerance to different herbicides including pendimethalin and metolachlor (Tharp and Kells 2000), bentazon and 2,4-D (Evers et al 1993), 2,4-D and dicamba (Griffin et al 1984), and MCPA and 2,4-DB (Conrad and Stritzke 1980); in all cases, yield and persistence of the legume were markedly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that some herbicides can have initial phytotoxic effects, although seedlings usually recover without severe damage, and yield loss are not observed (Díaz et al 1992;Ivany et al 2002;Thomas et al 1994;Tonks et al 1991;Volenberg et al 2002;Young et al 2003). In other studies, however, various clover species were exposed and evaluated for tolerance to different herbicides including pendimethalin and metolachlor (Tharp and Kells 2000), bentazon and 2,4-D (Evers et al 1993), 2,4-D and dicamba (Griffin et al 1984), and MCPA and 2,4-DB (Conrad and Stritzke 1980); in all cases, yield and persistence of the legume were markedly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Broadleaf weeds, such as thistles and Brassicaceae, are controlled with 2,4-DB. Flumetsulam and chlorimuron have also been recommended for controlling burning nettle, swinecress, and common chickweed, which are not controlled by 2,4-DB (Lopez and Romera 1993;Tonks et al 1991). In established alfalfa, clethodim and haloxyfop controlled grasses but did not increase forage yield (Foy and Witt 1992;Twidwell et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Así, el control químico de malezas puede ser una técnica eficaz y económica si el herbicida es totalmente selectivo para la planta forrajera, de modo que no presente efectos de fitotoxicidad que perjudiquen el desarrollo o su rendimiento (Verzig-nassi et al, 2005;Rivas Pantoja et al, 2009). Es sabido que el control químico de malezas es una herramienta habitual en otras especies cultivadas leguminosas como soja (Glycine max L.) (Young et al, 2003), alfalfa (Medicago sativa L.) (Wilson, 1981;Tonks et al, 1991) y trébol rojo (Trifolium pratense L.) (Ceballos et al, 2005), aunque en todos esos cultivos es esencial utilizar la dosis adecuada de herbicida que permita un eficiente control de malezas sin producir fitotoxicidad.…”
Section: Introductionunclassified